Review Of Cyber Attacks Classifications And Threats Analysis In Cyber-Physical Systems - Al-Mhiqani, Mohammed Nasser Ahmed; Ahmad, Rabiah; Zainal Abidin, Zaheera; Abdulkareem, Karrar Hameed (Inderscience Publishers, 2019)
Cyber-physical systems (CPSs) have been widely used in many different critical areas like smart grid, healthcare, aircraft and etc. and they played a significant role in our daily lives. However, the CPS systems currently are one of the critical hackers' targets that have a lot of incidents due of the high impacts of these systems. Several works have been conducted in CPS, but still, there is a lack of theories and tools that organisations and researchers can use to understand the nature of the new threats and the impacts of each danger. This article provides description of CPSs usage areas and security challenges in some of the critical CPS fields. Likewise, discusses frameworks and taxonomies that have been used for classifying cyber-attacks or incidents. As well, study and analyse threats that have been stated in the previous studies and research to understand the current status of the risks on CPS.